Electrical Conduction and Dielectric Properties in Piezoelectric Fibre Composites - Hammami, Helmi; Arous, Mourad; Lagache, Manuel; Kallel, Ali (Smart Materials for Energy, Communications and Security, 2008)
Smart structural composites are multifunctional structural materials which can perform functions such as sensing strain, vibration reduction and are essential because of their relevance to mitigation and structural vibration control. Piezoelectric fiber composites were developed to overcome drawbacks of typical monolithic piezoceramic (PZT) actuators. Piezoelectric fiber composites can improve the performance of various structures, and can be subject to wide temperature range where the thermoelastic behavior is important. A series of 1–3 connectivity PZT fibers/epoxy resin composites with different volume fraction is studied by means of dielectric spectroscopy in the wide frequency range 0.1 Hz–100 kHz and temperature varying from the ambient to 210°C. The conduction phenomenon is analyz ed using the “universal power law” and its scaling is studied by the Jonscher's universal power law. At low frequencies ac conductivity tends to be constant, while in the high frequency region verifies the exponential law of conductivity. In the intermediate frequencies, the examined systems exhibit strong dispersion with frequency and the produced fitting curves deviate from the experimental data by not being able to describe the recorded relaxation and pointing out that in the vicinity of the relaxation peaks the power law is not applicable. Finally, dipolar relaxation mechanisms and interfacial or Maxwell-Wagner-Sillars relaxation were revealed in the frequency range and temperature interval of the measurements.